Interface Engineering Toward Surface‐Activated Catalysts for Advanced Li–CO2 Batteries - Yanze Song; Bingyi Lu; Zhiwen Min; Haotian Qu; Yingqi Liu; Rui Mao; Yanli Chen; Yuanmiao Sun; Guangmin Zhou (Carbon Energy)
ABSTRACT Lithium–carbon dioxide (Li–CO2) batteries with high theoretical energy density are regarded as promising energy storage system toward carbon neutrality. However, bidirectional catalysts design for improving the sluggish CO2 reduction reaction (CO2RR)/CO2 evolution reaction (CO2ER) kinetics remains a huge challenge. In this work, an advanced catalyst with fast‐interfacial charge transfer was subtly synthesized through element segregation, which significantly improves the electrocatalytic activity for both CO2RR and CO2ER. Theoretical calculations and characterization analysis demonstrate local charge redistribution at the constructed interface, which leads to optimized binding affinity towards reactants and preferred Li2CO3 decomposition behavior, enabling excellent catalytic activity during CO2 redox. Benefiting from the enhanced charge transfer ability, the designed highly efficient catalyst with dual active centers and large exposed catalytic area can maintain an ultra‐small voltage gap of 0.33 V and high energy efficiency of 90.2%. This work provides an attractive strategy to construct robust catalysts by interface engineering, which could inspire further design of superior bidirectional catalysts for Li–CO2 batteries.